1990
DOI: 10.7164/antibiotics.43.88
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Escherichia coli to rifampicin and sorangicin A - a comparison.

Abstract: Sorangicin A, a macrolide polyether antibiotic and the ansamycin antibiotic rifampicin inhibit DNA-dependentRNApolymerase to a similar extent. Resistance to sorangicin A is due to a mutation in the RNApolymerase which renders the enzyme less sensitive. Parallel investigations with rifampicin revealed partial cross-resistance, which was more marked in sorangicin A-resistant mutants than in rifampicin-resistant mutants. Sorangicin A is a new type of macrolide polyether antibiotic isolated from the gliding bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…In view of their structural novelty these agents might therefore be expected to retain activity against rifampin-resistant isolates. However, there have been reports of cross-resistance between some of the older compounds described here and rifampin (13,24). We examined this in more detail by establishing whether the nonrifamycin-type RNA polymerase inhibitors were active against genetically defined rifampicin-resistant (rpoB) mutants of S. aureus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In view of their structural novelty these agents might therefore be expected to retain activity against rifampin-resistant isolates. However, there have been reports of cross-resistance between some of the older compounds described here and rifampin (13,24). We examined this in more detail by establishing whether the nonrifamycin-type RNA polymerase inhibitors were active against genetically defined rifampicin-resistant (rpoB) mutants of S. aureus.…”
mentioning
confidence: 99%
“…Therefore, before considering whether other RNA polymerase inhibitors might be developed, it is important to establish whether resistance to rifamycins, such as rifampin, also confers cross-resistance to the other agents. Some attempts to address this issue have been made (9,12,13,15,24). However, the data are incomplete and the genetic basis of resistance to rifamycins in those strains used for cross-screening has rarely been determined.…”
mentioning
confidence: 99%
“…It has also been observed that some rifampin-resistant mutations can confer sorangicin resistance, suggesting largely overlapping binding sites for these two drugs (31,127,145). However, the structures of these drugs are different and observation that some rifampin-resistant mutants are sorangicin sensitive, while most sorangicin-resistant mutations confer rifampin resistance, suggests that subtle differences exist with regard to their modes of action (145).…”
Section: Drug-resistant Rnap Mutantsmentioning
confidence: 99%
“…2), suggesting that the former might be able to adapt better than RIF to conformational change and mutations in RNAP (80). Studies on RIF and sorangicin against resistant mutant M. tuberculosis strains revealed that a narrower range of mutant strains were resistant to sorangicin than to RIF and proved that RIF was more sensitive to the change of shape of the binding pocket due to its rigid structure, while sorangicin displayed more conformational flexibility, as demonstrated by molecular dynamics simulations (80,82).…”
Section: Sorangicinmentioning
confidence: 99%